Assessment of Risk in Dryland Agriculture: a study of Anantapur district in Andhra Pradesh - D. Moses Shyam; I. Narender; G. V. Krishna Rao (Journal of Agricultural Extension Management, 2025)
Indian agriculture achieved an impressive growth following the green revolution but instability in production too has increased. With the advent of green revolution in our country, dry land agriculture as been conscious of increasing production and productivity by exposing the farmers to new dry land technologies. However, an intriguing feature is that dry land agriculture is subjected to high instability in production year- to- year even after the green revolution period. It was observed that drought has an invisible hand in limiting the production and the productivity. More over transition from subsistence to commercialized agriculture has resulted in market induced risk on farm. The welfare implication of risk holds that wider changes in prices and income affect the investment and rational planning of family living expenses